Social dynamics : a worktext on understanding culture, society and politics - Abulencia, Arthur S.; Padernal, Rowel S. (Quezon City : Brilliant Creations Publishing, Inc., 2016)
"A learning resource designed to provide student-centered and performance-based learning opportunities to both learners and educators. It aims to invite young people to explore the social world that we are part of and lead the students to develop a theoretical understanding of current social issues we are facing amid globalization."
Includes bibliography and glossary.
English text.
Keywords: Sociology; Anthropology